Breaking a magnetic zero locus: model operators and numerical approach. Issue 2 (31st October 2013) - Bonnaillie‐Noël, V.; Raymond, N.
<x xml:space="preserve">Abstract</x> This paper is devoted to the spectral analysis of a Schrödinger operator in presence of a vanishing magnetic field. The influence of the smoothness of the magnetic zero locus is studied. In particular, it is proved that breaking the magnetic zero locus induces discrete spectrum below the essential spectrum. Numerical simulations illustrate the theoretical results. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>